Quantitative Method for Simultaneous Analysis of Acetaminophen and 6 Metabolites. Issue 2 (April 2017) - Lammers, Laureen A.; Achterbergh, Roos; Pistorius, Marcel C. M.; Romijn, Johannes A.; Mathôt, Ron A. A.
Abstract : Background: Hepatotoxicity after ingestion of high-dose acetaminophen [N-acetyl- para -aminophenol (APAP)] is caused by the metabolites of the drug. To gain more insight into factors influencing susceptibility to APAP hepatotoxicity, quantification of APAP and metabolites is important. A few methods have been developed to simultaneously quantify APAP and its most important metabolites. However, these methods require a comprehensive sample preparation and long run times. The aim of this study was to develop and validate a simplified, but sensitive method for the simultaneous quantification of acetaminophen, the main metabolites acetaminophen glucuronide and acetaminophen sulfate, and 4 Cytochrome P450–mediated metabolites by using liquid chromatography with mass spectrometric (LC-MS) detection. Methods: The method was developed and validated for the human plasma, and it entailed a single method for sample preparation, enabling quick processing of the samples followed by an LC-MS method with a chromatographic run time of 9 minutes. The method was validated for selectivity, linearity, accuracy, imprecision, dilution integrity, recovery, process efficiency, ionization efficiency, and carryover effect. Results: The method showed good selectivity without matrix interferences. For all analytes, the mean process efficiency was >86%, and the mean ionization efficiency was >94%. Furthermore, the accuracy was between 90.3% and 112% for all analytes, and the within- and between-run imprecision were <20% for the lower limit of quantification and <14.3% for the middle level and upper limit of quantification. Conclusions: The method presented here enables the simultaneous quantification of APAP and 6 of its metabolites. It is less time consuming than previously reported methods because it requires only a single and simple method for the sample preparation followed by an LC-MS method with a short run time. Therefore, this analytical method provides a useful method for both clinical and research purposes.